Multiple origins of the sickle mutation: evidence from beta S globin gene cluster polymorphisms. - Wainscoat, J; Bell, J; Thein, S; Higgs, D; Sarjeant, G; Peto, T; Weatherall, D (1983)
Restriction site polymorphisms of the beta globin gene cluster of 244 Jamaican beta S chromosomes have been studied. Various patterns of restriction site polymorphisms (haplotypes) both 5' and 3' to the beta gene have been found. These two groups of haplotypes were found to be non-randomized with respect to each other. This is in contrast to normal beta A chromosomes where the 5' and 3' haplotypes are randomized. These findings together with the large number (18) of different beta S haplotypes found indicate that the beta S mutation probably has multiple origins.